If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5 + -1m) = 32 (5 * 2 + -1m * 2) = 32 (10 + -2m) = 32 Solving 10 + -2m = 32 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -2m = 32 + -10 Combine like terms: 10 + -10 = 0 0 + -2m = 32 + -10 -2m = 32 + -10 Combine like terms: 32 + -10 = 22 -2m = 22 Divide each side by '-2'. m = -11 Simplifying m = -11
| -2-4w=-5w-7 | | (2x-9)-(3x-3)=-(3x+3)-3x+9 | | 3=p*15 | | 6x+12y+15z= | | 11x+2=8x | | -9p=-10-10p | | t^2+16t+60= | | -3x=4y+8 | | 3(4g+6)=2+(6g+9) | | 10+n=-n | | 8-5(z-2)=-2(5z-2)-2 | | -6j+6=-8j | | 10x-8y=26 | | 10x+5=3+4x-8 | | -4+3f=2f | | 6(6x+1)=9(4x-3)+5 | | -7+6(-8n+8)=(-2+5)+7 | | C+2c+c=20 | | 7+19t-2=9t+107-7t | | x+(3)=-7 | | 5x*2-1+2x*2+x+5=0 | | 3(-3y-3)=-9+23 | | 20c-15c=10 | | 11=7x+1-5x | | 110-4x=170-8x | | -5a-4a+2a=14 | | -22=4x-6x-2 | | 2.7+10m=6.35 | | 9-2x=3(2x-5) | | 3(x-5)+2=7(2-x)+1 | | 4r+16=4r-32 | | 6-x-1=6-[x+1] |